e-Promotion: A Revolution In Technical Education Evolution - , Golahit S.B.2, Mahajan P.T.1 (International Journal of Scientific Research and Management (IJSRM), 2017)
Despite of increasing pressure related to enrollment in Technical Education, some Institutes of TechnicalEducation, successfully have taken on a corporate mentality to attract and retain high-quality studentsthrough their e-Promotion. Successful branding and marketing strategies have become most important forthe Institutes of Technical Education to appeal to a growing and diversified student and to differentiatefrom competitors. Effective branding can be helpful in increasing enrollment and in developingrelationships and bonding. This article explores internet based promotions that Technical Educationinstitutes have focused on branding and marketing initiatives and its influence on the students in selectinginstitute. It also focuses on effectiveness of internet based promotions. The research study showed thatInstitute Website and Social Networking are the most influential promotion tools for making theirdecision of selection than the other traditional promotion tools. In addition, these tools are reported to bevery powerful and effective in making satisfaction of decision of selection which is highly associatedwith such a promotion tools. More surprisingly, it is found to be productive in the rural area. This articlepresents an adaptation of established qualitative research methodsby a survey (through a structuredquestionnaire) of students who are presently enrolled (Current-students) and those who have completedtheir study (Post-students) belonging to the institutes offering Technical Education situated in Khandeshregion of India and affiliated to the North Maharashtra University, Jalgaon. The survey is delimited to theenrollments of Technical Education belonging to North Maharashtra University, Jalgaon and located inKhandesh region of India